Limb bone scaling in hopping macropods and quadrupedal artiodactyls. Issue 10 (24th October 2018) - Doube, Michael; Felder, Alessandro A.; Chua, Melissa Y.; Lodhia, Kalyani; Kłosowski, Michał M.; Hutchinson, John R.; Shefelbine, Sandra J.
Abstract : Bone adaptation is modulated by the timing, direction, rate and magnitude of mechanical loads. To investigate whether frequent slow, or infrequent fast, gaits could dominate bone adaptation to load, we compared scaling of the limb bones from two mammalian herbivore clades that use radically different high-speed gaits, bipedal hopping (suborder Macropodiformes; kangaroos and kin) and quadrupedal galloping (order Artiodactyla; goats, deer and kin). Forelimb and hindlimb bones were collected from 20 artiodactyl and 15 macropod species (body mass M 1.05–1536 kg) and scanned in computed tomography or X-ray microtomography. Second moment of area ( I max ) and bone length ( l ) were measured. Scaling relations ( y = ax b ) were calculated for l versus M for each bone and for I max versus M and I max versus l for every 5% of length. I max versus M scaling relationships were broadly similar between clades despite the macropod forelimb being nearly unloaded, and the hindlimb highly loaded, during bipedal hopping. I max versus l and l versus M scaling were related to locomotor and behavioural specializations. Low-intensity loads may be sufficient to maintain bone mass across a wide range of species. Occasional high-intensity gaits might not break through the load sensitivity saturation engendered by frequent low-intensity gaits.